Effectiveness of Mandala Coloring Intervention on Children’s Preoperative Anxiety: A Randomized Clinical Trial Study in Iran - Reihane Moghimian Shahrbabaki; Ali Omidi; Negin Shaterian; Zohreh Makarem (Iranian Journal of Nursing and Midwifery Research)
Background: Mandala coloring is a distraction strategy to reduce the anxiety in children. However, it has received little attention for the management of anxiety in hospitalized children. This study aimed to examine the effectiveness of mandala coloring on preoperative anxiety in children. Materials and Methods: This randomized controlled trial study was conducted using a pre-test–post-test design in two intervention and control groups. The 64 school-age children, who were admitted to the pediatric surgery ward in Mofid Hospital in Tehran, were allocated to the test and control groups, using a single-blind block randomized design. Children in the control group underwent routine preoperative visits. Meanwhile, the children in the intervention group, mandala coloring intervention was done at least one hour before entering the operating room for 15–20 minutes. The level of anxiety was measured through the Spielberger State-Trait Anxiety Inventory, before and after the intervention of both groups. Results were analyzed using t-test and Pearson correlation. Results: In the intervention group, there was a statistically significant in post-intervention than the pre-intervention and the children reported a lower level of anxiety (t = 4.51, df = 31, P = 0.01). But, after the intervention, there was not a statistically significant between the intervention and control groups in terms of average trait (t = 1.31, df = 61.86, P = 0.194) and state anxiety levels (t = -0.152, df = 58.94, P = 0.879). Conclusions: The results indicated that likely, mandala coloring intervention was not effective in reducing preoperative anxiety in children. Further studies are needed to more assess the effects of mandala coloring on anxiety of children undergoing surgery.